2016
DOI: 10.1007/s00429-016-1203-3
|View full text |Cite
|
Sign up to set email alerts
|

The association between stress and mood across the adult lifespan on default mode network

Abstract: Aging of brain structure and function is a complex process characterized by high inter- and intra-individual variability. Such variability may arise from the interaction of multiple factors, including exposure to stressful experience and mood variation, across the lifespan. Using a multimodal neuroimaging and neurocognitive approach, we investigated the association of stress, mood and their interaction, in the structure and function of the default mode network (DMN), both during rest and task-induced deactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 70 publications
1
28
1
Order By: Relevance
“…Previous studies reporting that a single ketamine treatment may alleviate treatment resistant depression by normalizing aberrant activity in DMN components and the frontal cortex [66][67][68]. Although it is well established that ketamine can decrease functional activity in the DMN and other brain regions [47][48][49][50][51][52][53][54][55][56][57][58][59][60], we found increased ReHo in the DMN in CTRS patients with TRD symptoms in this pilot study. We postulated that this seemingly contradictory finding may be related to neuropathological features of schizophrenia.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Previous studies reporting that a single ketamine treatment may alleviate treatment resistant depression by normalizing aberrant activity in DMN components and the frontal cortex [66][67][68]. Although it is well established that ketamine can decrease functional activity in the DMN and other brain regions [47][48][49][50][51][52][53][54][55][56][57][58][59][60], we found increased ReHo in the DMN in CTRS patients with TRD symptoms in this pilot study. We postulated that this seemingly contradictory finding may be related to neuropathological features of schizophrenia.…”
Section: Discussioncontrasting
confidence: 60%
“…The mPFC, anterior cingulate, posterior cingulate, precuneus, and angular gyrus, which have been identified as components of the DMN, and the OFC, which is part of the affective network, are key regions related to mood processing [47][48][49][50]. Notably, neural activities in the DMN and OFC have been reported to be markedly decreased in depressive patients [51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…While straightforward to implement in single-subject analyses, group ICA analyses are more complex and require choosing between several different workflows and algorithm definitions (Beckmann and Smith, 2004; Calhoun et al, 2009; Schöpf et al, 2010; Du et al, 2016). ICA methods also have been used extensively in rs-fMRI studies (Beckmann et al, 2005; Soares et al, 2016), task-based fMRI (Calhoun et al, 2008), and for artifact removal (Perlbarg et al, 2007; Feis et al, 2015; Pruim et al, 2015). …”
Section: Analysis Methodsmentioning
confidence: 99%
“…For this reason, resting state fMRI (rs-fMRI) analyses rely upon spontaneous coupled brain activity to reveal intrinsic signal fluctuations in the absence of external stimuli or demands of imposed tasks (Damoiseaux et al, 2006; Fox and Raichle, 2007; Schölvinck et al, 2010; van den Heuvel and Hulshoff Pol, 2010; Friston et al, 2014b). Complimentary approaches, combining rs-fMRI with functional deactivation (shifting from periods of stimulation to those of rest) also have been described to study functional activity transitions (Greicius and Menon, 2004; Anticevic et al, 2012; Soares et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Despite converging evidence on the involvement of these distributed networks in brain responses to stress [14,16,17], the effect of stress on their components is less clear [13,18]. For instance, considering the change in the brain activation, whereas Pruessner et al [19] and Koric et al [20] reported an elevated frontal activity in response to stress, Albert et al [21] and Qin et al [9] observed an opposite effect in this region.…”
Section: Introductionmentioning
confidence: 99%